Pengembangan Model Stimulasi Geometri Berbasis Pendekatan SAVI (Somatic, Auditory, Visual, Intelectual) untuk Anak Usia Dini - Winda Sherly Utami; Sri Indriani Harianja (PG-PAUD Trunojoyo, 2023)
This study aims (1) to analyze the need to stimulate geometry abilities in children aged 5-6 years, (2) to determine the level of feasibility and effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model to stimulate geometric abilities in children aged 5-6 years. This research is development research that refers to the ADDIE development model (analysis, design, development, implementation, and evaluation). The test subjects in this study consisted of 101 children aged 5-6 years in Pancung Sol District, Pesisir Selatan. Collecting data with interviews, questionnaires and observation. The research results obtained were (1) in stimulating the geometric abilities of children aged 5-6 years they needed the SAVI learning model, (2) the SAVI learning model was declared feasible and effective for stimulating geometric abilities in children aged 5-6 years based on the results of the N-Gain test with a value of 0.81 or 81% which is included in the high and effective category. Recommendations for future researchers to conduct similar research by developing other learning models, so that there are many learning models that can be used to stimulate the geometry abilities of children aged 5-6 years.